Relationship of Emotional Disturbance in Children with Hearing Impairment and Stress in Mothers - Mamoona Mushtaq, Najma Najam (Pakistan Journal of Psychology, 2014)
Anger assessment has got increasing attention of psychologists due to its great role in developing hypertension and heart diseases. In the present research, STAXI by Spielberger (1988) 44 items was translated and adapted into Urdu language to assess anger among hypertensive patients using back translation technique and validated through correlations, reliability analysis, factor analysis and independent samples t test. Reliability study was conducted by using alternate form method and sufficient alpha coefficients on subscales of STAXI were found. In the 2nd study a sample of 287 (hypertensive patients =163, non-hypertensive = 124) was taken from hospitals. Predictive validity was estimated by using logistic regression analysis with hypertensive and non hypertensive groups. Construct validity of the developed scale was established by using the method of contrasted groups. The alpha coefficients for factors of STAXI Urdu ranged from .61-.95. Exploratory factor analysis yielded a seven factor solution for Urdu STAXI. The factor structure was reasonably robust, whereas internal consistency and alternate form reliability were excellent. Logistic regression indicated that state anger, trait anger, anger-in, anger-control and anger turned out to be the strongest predictors of hypertension. Significant group differences on STAXI indicated construct validity of the adapted scale.